Direct effect of sclerostin on the mechanical loading response in bovine bone - Khalid, Kamarul Ariffin; Kogawa, Masakazu; Wijenayaka, Asiri R; Findlay, David M; Atkins, Gerald J (2012)
Sclerostin is expressed exclusively by mature osteocytes in bone. Our recent findings indicate that sclerostin targets pre-osteocytes/osteocytes to regulate bone mineralisation(1), osteoclast activity(2), and, potentially, osteocytic osteolysis(3). Sclerostin expression in vivo is associated with the osteocyte response to mechanical loading/unloading. The aim of this study was to examine the effects of sclerostin on loading-induced bone growth ex vivo. For this, 10x5mm bovine sternum trabecular bone cores were perfused with osteogenic media at 37"C for up to 3 weeks in individual bone culture chambers. The cores were divided into 3 groups; a) mechanically loaded (300 cycles, 4000 microstrain, 1 Hz/day), b) identical loading regime with continuous perfusion of 50 ng/ml recombinant human sclerostin and c) unloaded controls. Loading was accomplished using a Zetos(TM) bone loading system. Daily measurements of bone stiffness, media pH and ionic calcium concentrations were made. Histomorphometric assessment, including fluorochrome labelling analysis, was made at the end of the experiment.